NEUROPSYCHOLOGICAL ASSESSMENT IN BABIES: Identifyng early signs of Autistic Spectrum Disorder (ASD) - Neves , Raphaela Santos (2025)
This study aims to analyze the studies published in the last 5 years on the neuropsychological assessment of occurrence and early identification of characteristic signs of Autistic Spectrum Disorder (ASD). Through the Google Scholar and PubMed platforms, twelve articles published between 2015 - 2020 were selected for a survey, of which only two were carried out in Brazil. The applicable literature investigated the constructs related to the main changes identified in early screening, the relationship between prematurity and autism, as well as the importance of surveillance in children with older siblings within the spectrum. The results indicate changes mapped in the first months of life, such as social interaction, language, for example, highlight the importance of early assessment and intervention in the face of characteristic signs of ASD, some instruments to be used in the screening and diagnosis process. The study had some limitations related to the specificity of the theme, however, deepening about the possibilities of constructs to be taken by the neuropsychologist.